Environmental, Social, and Governance Disclosure on Firm Value in the Indonesian Stock Exchange - Siti Fatimah; Dian Fahriani; Kafidin Muzakki; Chairil Anwar (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
The purpose of the study is to investigate how environmental, social, and governance disclosures affect the firm value of companies in the basic materials industry that are listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024. This study used a causal associative design and a quantitative technique. Purposive sampling was used to choose the sample, which included 50 businesses with 250 firm-year observations. Tobin's Q was used to represent company value, while the GRI Standards 2021 disclosure index was used to quantify ESG disclosure. Multiple linear regression was used to analyse the data using IBM SPSS version 25. The findings demonstrate that Environmental Disclosure, Social Disclosure, and Governance Disclosure do not significantly impact firm value when tested individually. However, the three ESG dimensions jointly show a statistically significant association with firm value, although the model's explanatory power remains limited. By applying the GRI Standards 2021 framework with fresh empirical data from Indonesian Basic Materials sector firms during the post-pandemic period, and bolstering sustainability-related policies, this study adds to the body of ESG literature.